On the Fast Track to EU Accession : Macroeconomic Effects and Policy Challenges for Estonia - Taube, Gunther; Weber, Rene. (Washington, D.C. : International Monetary Fund, 1999)
This paper assesses the macroeconomic impact and policy challenges related to Estonia's prospective accession to the EU and its potential adoption of the euro. Our analysis of the trade, financial, and fiscal channels includes a model-based illustrative scenario using MULTIMOD. We conclude that the welfare enhancing effects for Estonia of further EU integration are likely to outweigh the drawbacks of more pronounced macroeconomic imbalances that could accompany this process. To smooth Estonia's accession-related adjustment, its fiscal and structural policies should be geared toward mitigating domestic demand pressures, promoting saving, and ensuring efficient public investment.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet